Correlation analysis of geomagnetic parameter with south atlantic anomaly region - Khairul Afifi Nasuddin,; Mardina Abdullah,; Nurul Shazana Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
South Atlantic Anomaly (SAA) region is describe as a region with weak Earth magnetic field. The method apply is power spectrum analysis. By applying the power spectrum analysis method, the value of spectral exponent, β is obtained. From the spectral exponent, β, the Hurst exponent can be determined. The research is conducted by studying the SAA region where comparisons is made between the middle latitude region and high latitude region. 2 active period has been research, 11 March 2011 and 29 May 2011 and 2 normal period has been studied, 9 March 2011 and 12 May 2011. The research conduct indicate the SAA region tend to be persistent and as the vertical field intensity and total field intensity increase, the region tend to have a mixture of antipersistent and persistent characteristic. The high latitude region in this research conduct indicate a tendency to be antipersistent. By conducting research on the SAA region, it can provide knowledge of the dynamics and conditions of our Earth. The SAA region is a region where it is exposed to energetic particles. Satellites passing through the SAA region are also vulnerable to danger. Therefore, the region conducted on the SAA region, can provide knowledge on the characteristics of the SAA region. Research on SAA may increase knowledge of the Earth’s magnetic field.